2020
DOI: 10.1186/s10152-020-0536-8
|View full text |Cite
|
Sign up to set email alerts
|

Antifouling and antibacterial activities of bioactive extracts from different organs of the sea cucumber Holothuria leucospilota

Abstract: In this study, antifouling and antibacterial properties of polar, semi polar and non-polar bioactive compounds derived from the sea cucumber Holothuria leucospilota were investigated. A series comprising n-hexane, ethyl acetate and methanol extracts from four different organs of sea cucumber (body wall, gonad, digestive tract and respiratory tree) were investigated for their antibacterial and antifouling activity against two species of microalgae, larvae of barnacle Amphibalanus amphitrite and a non-target org… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 45 publications
3
19
0
Order By: Relevance
“…For example, extracts of Holothuria parva have been shown to reduce the impact of electromagnetic radiation on the testes of male Balb/C mice ( Vasei et al, 2015 ). Recently the anti-fouling and anti-microbial potential of H. leucopsilota was investigated, and fatty acids and Terpenes identified in ethyl acetate extracts of the body wall showed strong activity against Barnacle larvae and Staphylococcus aureus ( Darya et al, 2020 ).…”
Section: Other Propertiesmentioning
confidence: 99%
“…For example, extracts of Holothuria parva have been shown to reduce the impact of electromagnetic radiation on the testes of male Balb/C mice ( Vasei et al, 2015 ). Recently the anti-fouling and anti-microbial potential of H. leucopsilota was investigated, and fatty acids and Terpenes identified in ethyl acetate extracts of the body wall showed strong activity against Barnacle larvae and Staphylococcus aureus ( Darya et al, 2020 ).…”
Section: Other Propertiesmentioning
confidence: 99%
“…Whereas, they reported that the Staphylococcus epidermidis was the most sensitive strain against the methanolic and ethyl acetate extracts. In addition, Darya et al ( 2020 ) reported antibacterial and antifouling activates of several extracts (especially ethyl acetate extract) from Holothuria leucospilota . They suggested that fatty acids and terpenes as the major detected compounds in the extract might be responsible for antibacterial and antifouling activities.…”
Section: Discussionmentioning
confidence: 99%
“…Natural products from Sea cucumbers have been widely investigated for their biological activities such as antibacterial (Mashjoor and Yousefzadi 2017 ), antialgal, antifungal (Han et al 2009 ; Mashjoor and Yousefzadi 2017 ), antitumoral (Tian et al 2005 ) and so forth. Terpenoids are one of the most investigated secondary metabolites of the sea cucumbers, which may be used as new possible antifouling agents (Mert Ozupek and Cavas 2017 ; Darya et al 2020 ). In this regard, triterpene glycosides and saponins derived from the sea cucumbers have been previously considered as suitable candidates for cytotoxic, antimicrobial and antifouling agents (Aminin et al 2015 ; Mert Ozupek and Cavas 2017 ; Bahrami et al 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…5). Darya et al (2020) reported that ethyl acetate extract of Holothuria leucospilota showed significant anti-algal activity against C.muelleri. The quick anti-algal activity of both the feather star species suggests the suitability against emergency control of algal blooms.…”
Section: Anti-algal Bioassaymentioning
confidence: 99%